One Pot, Simple, and Efficient Synthesis of 2-Azetidinones Mediated by 3-(Diethoxyphosphoryloxy)-1,2,3-benzotriazin-4-(3H)-one - Saraei, Mahnaz; Zarei, Maaroof; Zavar, Saleheh (Letters in Organic Chemistry, 2017)
Background: 2-Azetidinones (β-lactams) has occupied an important role in organic chemistry and drugs. β-Lactam antibiotics are extensively applied to fight against microorganisms as antibiotic drugs. The Staudinger's ketene-imine cycloaddition is one of the most common approaches in the synthesis of 2-azetidinones. The aim of this paper to describe a methodology based on the use of 3-(diethoxyphosphoryloxy)-1,2,3-benzotriazin-4-(3H)-one (DEPBT) for the synthesis of 2-azetidinones under mild reaction conditions at room temperature. Methods: The present methodology deals with one pot [2+2] ketene-imine cycloaddition reaction of imine and substituted ketene to synthesis of 2-azetidinones in mild condition at room temperature. In addition, detailed experimental procedures are provided. Results: A series of 2-azetidinones were synthesized in good to excellent yield via one pot [2+2] ketene-imine cycloaddition reactions. The obtained products were purified in good yield by simple crystallization. All the synthesized compounds were well characterized by spectral and physical data. Conclusion: A simple method for one-pot transformation of various carboxylic acids and imines to 2-azetidinones using 3-(diethoxyphosphoryloxy)-1,2,3-benzotriazin-4-(3H)-one (DEPBT) has been developed. The yield of [2+2] ketene-imine cycloaddition was good to excellent, and starting materials were readily available. An aqueous work up and simple crystallisation was sufficient to obtain pure products because DEPBT produces water-soluble by-products.
Keywords: Staudinger reaction